2015
DOI: 10.5430/jnep.v5n8p76
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity in women after an acute myocardial infarction

Abstract: Citation for the original published paper (version of record):Løvlien, M., Mundal, L., Hall-Lord, M-L. (2015) Physical activity in women after an acute myocardial infarction.. ABSTRACT Background: Physical activity is recognized as being important in reducing mortality after an acute myocardial infarction. The study aimed to describe younger and older women's leisure time physical activity after an acute myocardial infarction, their motivations and barriers for engaging in physical activity and to assess as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The NPC Scale can be used to evaluate the outcome of nursing education programs, to assess nurses' competences in relation to the needs in health care organizations and to identify self-reported competences. [7,[11][12][13] The English version of the NPC Scale is now ready to be used in a full-scale research project among English-speaking nurse students and/or registered nurses. An example is the European Network Nursing Academies (ENNA) who has decided to use the NPC Scale in a joint European research project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPC Scale can be used to evaluate the outcome of nursing education programs, to assess nurses' competences in relation to the needs in health care organizations and to identify self-reported competences. [7,[11][12][13] The English version of the NPC Scale is now ready to be used in a full-scale research project among English-speaking nurse students and/or registered nurses. An example is the European Network Nursing Academies (ENNA) who has decided to use the NPC Scale in a joint European research project.…”
Section: Discussionmentioning
confidence: 99%
“…The NPC Scale has proved to be reliable and valid, [7] and has been used in several published studies including both nursing students on the point of graduation and registered nurses with professional experience, [11][12][13] as well as in publications in process by Theander et al [14] and Nilsson et al [15] Furthermore, the NPC Scale has been presented at both national medical conferences [16] and international nursing conferences, [17] and has yielded great interest from researchers in Europe, South and North America, and Asia. Therefore, the Swedish NPC research group decided to translate the NPC Scale into English to facilitate international use of the instrument.…”
Section: Introductionmentioning
confidence: 99%
“…, Løvlien et al . ). It has been reported that low scores on health‐related quality of life (HRQL) and sense of coherence (SOC) predict morbidity and mortality in coronary patients, even in the elderly, which establishes good HRQL and SOC as important outcomes for these patients.…”
Section: Introductionmentioning
confidence: 97%